Fast pyrolysis of biomass : advances in science and technology - Brown, Robert C.; Wang, Kaige (Royal Society of Chemistry, 2017)
Fast pyrolysis and related catalytic pyrolysis are of increasing interest as pathways to advanced biofuels that closely mimic traditional petroleum products. This book will be of interest to advanced students and researchers of the science behind renewable fuel technology, and particulary the thermochemical processing of biomass.
Keywords: Pyrolysis.; Biomass.; elektronické knihy; electronic books